GAMBARAN PENERAPAN PEMBERIAN INFORMASI BERDASARKAN KONSEP FAMILY CENTERED CARE PADA ANAK DENGAN PENYAKIT AKUT SELAMA HOSPITALISASI - Natasya, Prianti; Deli, Hellena; Hasanah, Oswati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Hospitalization can have an adverse effect on children and parents, especially for parents who do not get complete information about child care while in hospital, so that aplication of family centered care (FCC) concept should be applied. This study aims to describe the application of information based on the FCC concept in children with acute illness during hospitalization. This study used a quantitative descriptive design with a cross sectional approach. The study was conducted in the Lili Room of Arifin Achmad Hospital using a snowball sampling technique with a sample of 40 people based on the inclusion criteria. The measuring instrument used was likert scale questionnaire giving information based on the FCC concept. The analysis used was univariate analysis to analyze the frequency distribution of each variable. The results showed that the description of the application of information to conditions, developments and actions taken in children were mostly in the poor category (52.5%), the description of nurses' behavior about the application of information to parents was mostly in the good category (60%), the description of the application of information to family involvement in child care plans was in the good category (97.5%). It is recommended for nurses as health workers who often correspond to patients and families for always provide information about child care during hospitalization and health education in accordance with the background of patients and families.Keywords : Children, Family Centered Care, Hospitalization, Information